Former Government Official or Politician Director and Audit Committee Relationship with CEO’s Discretion and Real Earnings Management - Pugatekaew, Konnut (Creative Business and Sustainability Journal, 2021)
The research examined the CEO’s shareholding, directors, and audit committee who were former government officials or politicians on real earnings management (REM), and the influence of the directors and the committee on CEO’s discretionary in REM of Thai listed companies during the period of 2017 to 2019. Multiple regression analysis confirmed a relationship. The results indicated that CEO was not related to REM. The directors and audit committee were negatively related to REM. In addition, the directors moderated on rising CEO’s discretionary in REM, while the committee had a moderator effect negatively on the discretion in REM. The key highlight from this research was the directors may be persuaded to collaborate with the CEO on real earnings management. The results provided an advantage for enriching the Agency Theory, and the Resource Dependence Theory under the current situation. In addition, the regulator reviews the directors’ and audit committee members’ qualifications, also a piece of additive information for investors to make investment decisions.